1999
DOI: 10.1111/j.1528-1157.1999.tb02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of Controlled Trials of Gabitril (Tiagabine): A Clinician's Viewpoint

Abstract: Summary: A recent problem for doctors has been the choice of which new antiepileptic drug (AED) to select for treatment of pharmacoresistant epilepsy. This article summarizes the clinical experience to date regarding the efficacy and safety of tiagabine (TGB; Gabitril) as adjunctive therapy in patients with partial-onset seizures. In its early Phase I1 development, TGB was evaluated in two multicenter pilot studies. Each had an open-label enrichment phase followed by a treatment phase with randomized, double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
1
13
0
4
Order By: Relevance
“…The clinical relevance of these data is clear for the action of TGB on generalized seizures. The drug was successfully tested in patients with intractable partial seizures, and it was also found to be effective against secondary generalization (5,6,30). Our results regarding the efficacy of TGB against minimal seizures are in agreement with those of Smith et al (31), who found that the drug was effective against photomyoclonic seizures in baboons.…”
Section: Discussionsupporting
confidence: 90%
“…The clinical relevance of these data is clear for the action of TGB on generalized seizures. The drug was successfully tested in patients with intractable partial seizures, and it was also found to be effective against secondary generalization (5,6,30). Our results regarding the efficacy of TGB against minimal seizures are in agreement with those of Smith et al (31), who found that the drug was effective against photomyoclonic seizures in baboons.…”
Section: Discussionsupporting
confidence: 90%
“…Yet as recently reviewed by van den Pol (86), the role of GABA and glutamate in regulating energy balance has yet to be determined. It is unlikely that the ability of VPA to induce weight gain is solely due to increased GABA transmission because other anticonvulsants that increase GABA, including tiagabine, are not reported to induce weight gain (87). To determine whether an acute reduction in serum leptin levels by VPA correlates with an increase in appetite, clinical studies are required that measure leptin levels immediately after VPA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although this theory can explain weight gain related to some GABA-enhancing drugs including VPA and gabapentine [15], this is not the sole mechanism. Other antiepileptic drugs that increase GABA, such as tiagabine, do not induce weight gain [36]. …”
Section: Possible Mechanisms Underlying Vpa-induced Weight Gainmentioning
confidence: 99%